2014
DOI: 10.1002/dvdy.24229
|View full text |Cite
|
Sign up to set email alerts
|

Microarray identification of novel genes downstream of Six1, a critical factor in cranial placode, somite, and kidney development

Abstract: Background Six1 plays an important role in the development of several vertebrate organs, including cranial sensory placodes, somites and kidney. Although Six1 mutations cause one form of Branchio-Otic Syndrome (BOS), the responsible gene in many patients has not been identified; genes that act downstream of Six1 are potential BOS candidates. Results We sought to identify novel genes expressed during placode, somite and kidney development by comparing gene expression between control and Six1-expressing ectode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 108 publications
0
31
3
Order By: Relevance
“…Our finding that many of the presumptive direct target genes of Six1 or Eya1 are not up-regulated in the absence of CHX indicates that without blocking protein synthesis it is not possible to reliably identify direct target genes, presumably due to the existence of indirect interactions with such targets. We believe that this is one of the reasons why our findings differ substantially from the study of Yan et al (2015) , which analysed differentially expressed genes in Xenopus animal cap explants after overexpression of Six1 without first blocking protein synthesis. None of the transcription factors in our prioritised list was identified in the study by Yan et al (2015) ; and we found none of the transcription factors differentially expressed in their study.…”
Section: Discussioncontrasting
confidence: 72%
“…Our finding that many of the presumptive direct target genes of Six1 or Eya1 are not up-regulated in the absence of CHX indicates that without blocking protein synthesis it is not possible to reliably identify direct target genes, presumably due to the existence of indirect interactions with such targets. We believe that this is one of the reasons why our findings differ substantially from the study of Yan et al (2015) , which analysed differentially expressed genes in Xenopus animal cap explants after overexpression of Six1 without first blocking protein synthesis. None of the transcription factors in our prioritised list was identified in the study by Yan et al (2015) ; and we found none of the transcription factors differentially expressed in their study.…”
Section: Discussioncontrasting
confidence: 72%
“…Since several large-scale screens in multiple animals have revealed many hundreds of Six1 transcriptional targets in a variety of tissues (e.g. Ando et al, 2005;Jusiak et al, 2014;Yan et al, 2015;Riddiford and Schlosser, 2016), sorting out the details of the Six1 gene regulatory network involved in craniofacial tissue development is an important next step.…”
Section: Effects On Craniofacial Gene Expressionmentioning
confidence: 99%
“…Although flies do not have the equivalent of cranial sensory placodes, we speculate that some of these genes may prove important in the transcriptional regulation of vertebrate placode development because of the significant conservation of many gene regulatory networks between flies and vertebrates. Using a different approach, we recently conducted an expression screen to identify potential new targets of Six1 in Xenopus ectodermal explants, and identified 72 up-regulated and 58 down-regulated genes (Yan et al, 2014). Like the fly study, most candidates are of unknown function, but over 30 of these genes are expressed in the PPE and placodes, suggesting they may be part of the placode transcriptional network.…”
Section: Induction and Specification Of The Pre-placodal Fieldmentioning
confidence: 99%